Ultrastiff, Strong, and Highly Thermally Conductive Crystalline Graphitic Films with Mixed Stacking Order. Issue 29 (3rd June 2019) - Wang, Bin; Cunning, Benjamin V.; Kim, Na Yeon; Kargar, Fariborz; Park, Sun‐Young; Li, Zhancheng; Joshi, Shalik R.; Peng, Li; Modepalli, Vijayakumar; Chen, Xianjue; Shen, Yongtao; Seong, Won Kyung; et al.
Abstract: A macroscopic film (2.5 cm × 2.5 cm) made by layer‐by‐layer assembly of 100 single‐layer polycrystalline graphene films is reported. The graphene layers are transferred and stacked one by one using a wet process that leads to layer defects and interstitial contamination. Heat‐treatment of the sample up to 2800 °C results in the removal of interstitial contaminants and the healing of graphene layer defects. The resulting stacked graphene sample is a freestanding film with near‐perfect in‐plane crystallinity but a mixed stacking order through the thickness, which separates it from all existing carbon materials. Macroscale tensile tests yields maximum values of 62 GPa for the Young's modulus and 0.70 GPa for the fracture strength, significantly higher than has been reported for any other macroscale carbon films; microscale tensile tests yield maximum values of 290 GPa for the Young's modulus and 5.8 GPa for the fracture strength. The measured in‐plane thermal conductivity is exceptionally high, 2292 ± 159 W m −1 K −1 while in‐plane electrical conductivity is 2.2 × 10 5 S m −1 . The high performance of these films is attributed to the combination of the high in‐plane crystalline order and unique stacking configuration through the thickness. Abstract : Stacked chemical vapor deposition (CVD) graphene when heat‐treated results in a macroscale graphitic film with mixed AB/incommensurate stacking through each layer but near‐perfect in‐plane order. This graphitic film has mechanical performance greatly exceeding all macroscale layered graphitic films, and an exceptionally high in‐plane thermal conductivity.